Investigating the effect of 8 weeks of moderate resistance training (MRT) and Lactobacillus Reuteri probiotic on the serum concentration of liver enzymes Alanine transaminase and Aspartate transaminase and weight changes in male Wistar rats with non-alcoh - Bargir, Akram; Ghazalian, Farshad; Keyvani, Hossein; Abed Natanzi, Hossein; Gholami, Mandana (Researcher Bulletin of Medical Sciences, 2025)
Objective: The aim of this study was investigating the effect of 8 weeks of moderate resistance training (MRT) and Lactobacillus Reuteri probiotic on the serum concentration of liver enzymes and weight changes in male Wistar rats with non-alcoholic fatty liver disease (NAFLD). Materials and Methods: This research was conducted on 32 male Wistar rats aged 8 to 10 weeks with a weight range of 230 to 300 grams. Male rats were randomly divided into 4 groups of 8. All animals were weighed at the beginning and weekly using a digital scale. Serum levels of liver enzymes were checked at the beginning, middle and end of the study. Results: In general, the findings of this study showed that at the end of the intervention, the level of ALT was significantly reduced in the groups receiving supplements and resistance training, but the serum level of AST was significantly reduced only in the group receiving probiotic supplements (P<0.05). Changes in weight also showed a significant increase in all 4 groups at the end of the eighth week. Conclusion: The findings of the present research showed that 8 weeks of moderate intensity resistance training and Lactobacillus Reutteri probiotic supplement alone improved liver enzyme function (especially ALT serum level) in rats with non-alcoholic fatty liver disease.